Checklists of Fish Species Infected with the Fish Lice Genus Argulus Müller O.F., 1785 (Crustacea: Argulidae) in Iraq: Checklists of Fish Species Infected with the Fish Lice in Iraq - Mhaisen , Furhan T. (Iraqi Journal of Aquaculture, 2024)
For preparing this article, 47 references dealing with the occurrence of species of the fish lice genus Argulus Müller O.F., 1785 infecting fish species in Iraq, until the end of 2024, were consulted. A total of 18 fish species were found to be infected with three species of this genus: A. coregoni. A. foliaceus and A. japonicus, in addition to some unidentified species of this genus. These Argulus species were recorded from one, 18 and three fish host species, respectively, in addition to unidentified Argulus species from four fish species. Such parasites were reported from the infected fishes in different water bodies (rivers, canals, lakes, marshes and drainage networks) and from some fishponds and hatchery in addition to some fishes from fish markets in different parts of Iraq. Ten of these fish species were infected with only one Argulus species, while eight fish species were infected with two Argulus species.